The influence of evaporation from porous concrete on air temperature and humidity. (15th March 2022) - Yang, Qiuxia; Dai, Fan; Beecham, Simon
Abstract: Porous concrete is increasingly being used as a more sustainable surfacing alternative to asphalt and other impermeable materials. This is because, not only does it provide source control of stormwater, but it also has the potential to help mitigate the urban heat island effect through the process of evaporative cooling. This experimental investigation examines how evaporation from these systems is affected by the availability of water within the porous concrete and the influence this has on the surrounding environment, particularly in terms of air temperature and humidity. The effect of a dual layer porous concrete on evaporation rates is also assessed, which is important because the dual layer system is a relatively new development that is now being used in many parts of the world. It was found that both evaporation rate and evaporative cooling were strongly influenced by water availability near the upper surface of the porous concrete and under these conditions significant air temperature reductions can be achieved. It was also found that having a dual layered porous concrete system did not have a considerable effect on evaporation rates in this study, probably because of the relatively large thickness of the upper layer. Highlights: Evaporation rate is greatest when water is in the upper 13 mm of concrete surface. Ambient air temperature is cooled by up to 12 °C when water is near surface. Having dual porous concrete layers does not affect evaporation rates.